Identification of possible siRNA molecules for TDP43 mutants causing amyotrophic lateral sclerosis: In silico design and molecular dynamics study. (April 2016) - Bhandare, Vishwambhar Vishnu; Ramaswamy, Amutha
Graphical abstract: Highlights: Design of siRNAs for tdp43 mutants causing ALS disorder is proposed. Analysis initiated at the genetic level after identifying the respective codons for the mutants based on minimum free energy and probabilistic approach. Elucidation of target accessibility of the identified siRNA. Evaluation of the ability of siRNA to interact with target mRNA via molecular dynamics and thermo-physical analyses. To propose the best possible siRNA candidates for RNAi therapy. Abstract: The DNA binding protein, TDP43 is a major protein involved in amyotrophic lateral sclerosis and other neurological disorders such as frontotemporal dementia, Alzheimer disease, etc . In the present study, we have designed possible siRNAs for the glycine rich region of tardbp mutants causing ALS disorder based on a systematic theoretical approach including (i) identification of respective codons for all mutants (reported at the protein level) based on both minimum free energy and probabilistic approaches, (ii) rational design of siRNA, (iii) secondary structure analysis for the target accessibility of siRNA, (iii) determination of the ability of siRNA to interact with mRNA and the formation/stability of duplex via molecular dynamics study for a period of 15 ns and (iv) characterization of mRNA–siRNA duplex stability based on thermo-physical analysis. The stable GC-rich siRNA expressed strong binding affinity towards mRNA and forms stable duplex in A-form. The linear dependence between the thermo-physical parameters such as T m, GC content and binding free energy revealed the ability of the identified siRNAs to interact with mRNA in comparable to that of the experimentally reported siRNAs. Hence, this present study proposes few siRNAs as the possible gene silencing agents in RNAi therapy based on the in silico approach.